2023
DOI: 10.1002/adpr.202200293
|View full text |Cite
|
Sign up to set email alerts
|

Broadband 2D n × n Vortex Arrays Generated from an Efficient Petal‐Like Raman Laser with an Astigmatic Mode Convertor

Abstract: Crisscross vortex arrays have well-defined arrangements of vortices, are ideal light sources for efficiently manipulating multiple microparticles, assemble microprocessing, and optical communications. However, the output power of crisscross vortex arrays is low and laser operating wavelength is limited by the narrow emission spectrum of Nd:YVO 4 crystal.The operating wavelength of optical vortex arrays expands their applications and various methods such as frequency doubling; stimulated Raman scattering (SRS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…[20,33] A 1-mm-thick Yb:YAG crystal doped with 10 at.% Yb 3+ ions was used as active medium for generating broadband Raman laser taking advantage of the broad emission band of Yb:YAG crystal. [25,34] M1 and M2 are coatings as the cavity mirrors and L R indicates the thickness of YVO 4 crystals. Film with high reflectivity at 1030-1100 nm and anti-reflection at 940 nm was coated on Yb:YAG crystal to act as front cavity mirror, M1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[20,33] A 1-mm-thick Yb:YAG crystal doped with 10 at.% Yb 3+ ions was used as active medium for generating broadband Raman laser taking advantage of the broad emission band of Yb:YAG crystal. [25,34] M1 and M2 are coatings as the cavity mirrors and L R indicates the thickness of YVO 4 crystals. Film with high reflectivity at 1030-1100 nm and anti-reflection at 940 nm was coated on Yb:YAG crystal to act as front cavity mirror, M1.…”
Section: Methodsmentioning
confidence: 99%
“…The achieved optical conversion efficiency for vector vortex lasers with RP-ARP and AP-AAP is comparable to the high-order petallike Yb:YAG/YVO 4 Raman microchip laser by shifting focal spot away from Yb:YAG crystal surface. [25,26] Therefore, efficient performance of HP vector vortex Raman laser has been achieved. Although there is a severe thermal effect in the Yb:YAG/YVO 4 Raman microchip laser at high pump power, the performance of HP vector vortex Raman microchip laser can be further enhanced by optimizing pump beam spot to increase pump power intensity and maintaining good mode matching between pump beam and LG 0,1 vortex laser beam.…”
Section: Output Power Of Hp Vector Vortex Raman Lasersmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonlinear frequency conversion methods [19,20], such as stimulated Raman scattering, are a useful tool for achieving an easy frequency conversion, orbital angular momentum transfer and even topological charge doubling. In 2013, Andrew et al [21] from Macquarie University used a 20 mm long Nd:GdVO 4 as a Raman and lasing medium, which as a first-Stokes emission produced an output power of 380 mW and a fundamental beam of 400 mW under the incident pump power of 6.8 W. The LG 01 mode was preserved for the fundamental and the Stokes fields, respectively, which showed that the orbital angular momentum in the fundamental fields was transferred to the Stokes field.…”
Section: Introductionmentioning
confidence: 99%